2021
DOI: 10.3390/ncrna7010010
|View full text |Cite
|
Sign up to set email alerts
|

Fusion Genes and RNAs in Cancer Development

Abstract: Fusion RNAs are a hallmark of some cancers. They result either from chromosomal rearrangements or from splicing mechanisms that are non-chromosomal rearrangements. Chromosomal rearrangements that result in gene fusions are particularly prevalent in sarcomas and hematopoietic malignancies; they are also common in solid tumors. The splicing process can also give rise to more complex RNA patterns in cells. Gene fusions frequently affect tyrosine kinases, chromatin regulators, or transcription factors, and can cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 147 publications
0
48
0
Order By: Relevance
“…Chimeric RNAs are evidently involved in cancer [17,18,87,88]. In cancer cells, chimeric RNAs could either produce oncogenic chimeric protein or oncogenic lncRNA, impacting cancer evolution and heterogeneity [25,64,86,[89][90][91].…”
Section: How Could Chimeric Rnas Lead To Cancer Evolution?mentioning
confidence: 99%
“…Chimeric RNAs are evidently involved in cancer [17,18,87,88]. In cancer cells, chimeric RNAs could either produce oncogenic chimeric protein or oncogenic lncRNA, impacting cancer evolution and heterogeneity [25,64,86,[89][90][91].…”
Section: How Could Chimeric Rnas Lead To Cancer Evolution?mentioning
confidence: 99%
“…Recent studies identified several chimeric RNAs in different cancers that are associated with oncogenesis, cancer heterogeneity, and the evolution of cancer drug resistance [ 8 , 43 ]. The appearance of chimeric RNAs in a particular cell can promote functional expansion and increase phenotypic diversity to help the cell to survive in the face of new stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Fusion genes have been considered to play a role in driving tumor initiation, metastasis, and resistance to therapy in solid cancers as well as in hematological malignancies [ 19 , 20 ]. A number of genes, including kinases, transcription factors, and cell cycle regulators, generate fusion genes in many types of cancers, and the resulting structural alteration and different regulation can cause tumorigenesis and progression.…”
Section: Discussionmentioning
confidence: 99%